Active Food Packaging Based on Biopolymers and Aroma Compounds: How to Design and Control the Release - Wicochea-Rodríguez, Jose Daniel; Chalier, Pascale; Ruiz, Thierry; Gastaldi, Emmanuelle (Frontiers in Chemistry, 2019)
Aroma compounds are known to be efficient active agents for a broad range of applications (antimicrobial, anti-oxidant, insect repellent…) that are highly sought when aiming at extending shelf life of food or biological products. However, they are intrinsically odorant and volatile at ambient temperature, which restricts the processing routes used to introduce them in a polymeric matrix and can affect their mode of action and limit efficiency. Indeed, due to their high sensitivity toward temperature they can be lost or transformed during processing. Acting after being released in the headspace, their concentration has to be controlled to avoid any odorant contamination of the targeted products. Hence, the ability for an aroma compound to be retained in a polymeric matrix, and then released when submitted to a triggering effect, are the two main requirements that should be satisfied. The volatile nature of the aroma compound offer the possibility when introduce in the packaging to act by direct or indirect contact with the product and thus to be used in different ways; as a coating layer directly applied on the product surface, as a self-supported film or as coated paper when associated with a paper sheet, as well as an object that could be inserted in the package. As biopolymers such as proteins and polysaccharides are able to retain aroma compounds but also to favor their release by modification of their structure when RH and temperature change, they are relevant carriers of these specific aroma compounds. Examples of how active packaging systems with limonene, eugenol and carvacrol as active agent were designed and elaborated will be presented with special focus on the processing conditions and the way to improve their retention and to control the release (biopolymer nature, cyclodextrin clay addition…). Avrami’s equation has been used to model the transfer of aroma compound and to advantageously compare it taking into account the mechanism in relation to the biopolymer structural changes.